Between Enjoyment and Comprehension: Students’ Perceptions of English Songs in Developing Listening Skills - Suwarsito; Viviana Lisma Lestari (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
This study explores how English Education students at UIN Syarif Hidayatullah Jakarta perceive and experience the use of English songs as a medium to improve their listening skills. Despite growing enthusiasm for song-based learning, debates remain regarding its effectiveness beyond motivation. Adopting a qualitative descriptive design, the study involved five final-year students selected through purposive sampling. Data were collected through semi-structured interviews, validated by an expert in listening pedagogy, and analyzed thematically using Miles and Huberman’s (1994) framework. The analysis yielded five major themes: (1) enjoyment and motivation, (2) vocabulary and pronunciation development, (3) listening comprehension challenges, (4) learning strategies, and (5) autonomy and habit formation. The findings reveal that while English songs enhance enjoyment, reduce anxiety, and provide authentic linguistic exposure, students also face difficulties related to speed, slang, and cultural references. Nevertheless, they develop personal strategies—such as repeated listening and lyric translation—that foster autonomy and sustained engagement. Overall, the study concludes that English songs serve a dual pedagogical function: they act as affective catalysts and as authentic input for listening development. Pedagogically, teachers are encouraged to integrate songs purposefully, balancing enjoyment with structured linguistic and reflective activities to maximize their instructional potential.